Quantitative proteomics using SILAC: Principles, applications, and developments. Issue 18 (14th July 2015) - Chen, Xiulan; Wei, Shasha; Ji, Yanlong; Guo, Xiaojing; Yang, Fuquan
Abstract : SILAC is based on direct addition of selected stable isotope amino acids into the cell culture medium, allowing superior quantitative analysis of the cellular proteome compared to other labeling methods. The great advantages of SILAC lie in its straight‐forward implementation, quantitative accuracy, and reproducibility over chemical labeling or label‐free quantification strategies, favoring its adoption for proteomic research. SILAC has been widely applied to characterize the proteomic changes between different biological samples, to investigate dynamic changes of protein PTMs, to distinguish specific interacting proteins in interaction proteomic analysis, and to analyze protein turnover in the proteome‐wide scale. The present review summarizes the principles of SILAC technology, its applications in biological research, and the present state of this technology.